Analysis of TMT heterogeneity and IPO underpricing of listed companies in the low carbon economy sector: Evidence from China’s stock market - Zhou, Xiaohua; Feng, Guan; Ren, Yong (Frontiers in Energy Research, 2023)
The issue pricing is an important part of the operation of the securities market. Its pricing is directly related to the interests of issuers, investors and underwriters, as well as the regulatory and resource allocation functions of the securities issue market. When the industry expectation difference is large, the company has greater TMT (Top Management Team) heterogeneity. When the market expectation gap expands, the possibility of risk conversion increases. IPO (Initial Public Offering) underpricing occurs in the stocks of developed countries, developing countries and emerging countries. Because the issuer and the underwriter investors have different information, for example, the information advantage of the underwriter will bring risks to investors when they buy IPO stocks. IPO underpricing is the compensation for the risks brought by asymmetric information. How the listed company's own value affects the IP underpricing has received little attention. This paper will fill this gap and empirically study the impact of executive team management ability on IPO underpricing. Therefore, starting from the Chinese stock market, this paper studies the evidence of vertical parallel executives, heterogeneity of senior management teams and IPO underpricing. Finally, the average values of NCSKEW (C1) and DUVOL (C2) are -0.301 and -0.203 respectively, which are close to the descriptive statistics studied. The dependent variable data in this paper has a certain reliability. The minimum value of NCSKEW is -0.361, and the maximum value is 0.392, indicating that the fragmentation risk of different stocks is relatively large.